Comparison of different diagnostic methods in infants with Cholestasis - Dehghani, Seyed Mohsen (World journal of gastroenterology : WJG, 2006)
AIM： To evaluate different methods in differentiating idiopathic neonatal hepatitis from biliary atresia. METHODS： Sixty-five infants with cholestatic jaundice and final diagnosis of idiopathic neonatal hepatitis and biliary atresia were studied prospectively from September 2003 to March 2006. A thorough history and physical examination were undertaken and the liver enzymes were examined. All cases underwent abdominal ultrasonography, hepatobiliary scintigraphy, and percutaneous liver biopsy. The accuracy, sensitivity, specificity and predictive values of these various methods were compared. RESULTS： There were 34 girls and 31 boys, among them 46 subjects had idiopathic neonatal hepatitis （age, 61 ± 17 d） and 19 had biliary atresia （age, 64 ± 18 d）. The mean age at onset of jaundice was significantly lower in cases of biliary atresia when compared to idiopathic neonatal hepatitis cases （9 ±13 d vs 20 ± 21 d; P = 0.032）. The diagnostic accuracy of different methods was as follows： liver biopsy, 96.9%; clinical evaluation, 70.8%; ultrasonography, 69.2%; hepatobiliary scintigraphy, 58.5%; and liver enzymes, 50.8%. CONCLUSION： Our results indicate that clinical evaluation by an experienced pediatric hepatologist and a biopsy of the liver are considered as the most reliable methods to differentiate idiopathic neonatal hepatitis and biliary atresia.